Insights from sloshing experiments in a rectangular hydrophobic tank - Korkmaz, Fatih C.; Guzel, Bulent (ELSEVIER SCIENCE INC, 2023)
The wave impingement on the side walls due to the oscillation of a rectangular tank under harmonic sway motion is analysed experimentally with hydrophobic coated and uncoated tank surfaces. Impact pressures and free surface deformations are compared in three water filling levels over an excitation frequency range encompassing the first natural frequency. The reduced hydrodynamic loads acting on the tank walls are observed under hydrophobic effects and discussed in detail. Experimental observations clearly indicate that there is a strong effect of the solid surface properties on the free surface elevation, wave generation and pressure distribution. In particular, major changes have been traced around the resonance frequency due to more dominant tangential flow and altered wave form, which results in lower peak pressure values with increased water movement within the tank under the hydrophobic effects.
Keywords: Sloshing; Hydrophobic coating; Pressure measurement; Free surface deformation; WAVE IMPACT; LOADS; Thermodynamics; Engineering; Physics